Предмет: Алгебра, автор: csmangust

Решить систему уравнений!

Приложения:

Ответы

Автор ответа: mmb1
0

(x + y + z)² = (x + y)² + 2(x + y)z + z² = x² + 2xy + y² + 2xz + 2yz + z² = x² + y² + z² + 2(xy + xz + yz)

-----

x² + xy + xz = y      x(x + y + z) = y

y² + yz + yx = z      y(x + y + z) = z

z² + zx + zy = x       z(x + y + z) = x

всё складываем

x² + xy + xz + y² + yz + yx + z² + zx + zy = z + y + x

x² + y² +z² + 2(xy + xz + yz) = x + y + z

(x + y + z)² = x + y + z

1. x + y + z = 0

x(x + y + z) = y

y(x + y + z) = z

z(x + y + z) = x

0x = y

0y = z

0z = x

x=y=z=0

2. x + y + z = 1

x = y

y = z

z = x

x² + x² + x² = x

3x² = x

x = 0  y = 0 y = 0

x = 3 не корень

ответ (0 0 0)

Похожие вопросы
Предмет: Математика, автор: nabolelo